2014
DOI: 10.1179/1432891714z.000000000776
|View full text |Cite
|
Sign up to set email alerts
|

Self-organised nanoporous anodic films on superaustenitic stainless steel

Abstract: Self-organised nanoporous anodic films were fabricated on 904L superaustenitic stainless steel by the electrochemical treatment in ethylene glycol electrolyte containing perchloric acid. The effects of experimental conditions, such as electrolyte temperature and applied voltage on nanoporous morphology, were studied by the way of scanning electron microscopy. The results show that lower solution temperature promotes formation of orderly nanopores. Nanoporous anodic films cannot be formed, and pitting will appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…All these results were reported for samples treated for 600 s. A sample was also treated for 300 s, and un-ordered surface morphology was observed. Lu et al [ 39 ] also reported that pitting appeared on this type of stainless steel when the electrolyte temperature was about 40 °C.…”
Section: Literature Surveymentioning
confidence: 94%
See 3 more Smart Citations
“…All these results were reported for samples treated for 600 s. A sample was also treated for 300 s, and un-ordered surface morphology was observed. Lu et al [ 39 ] also reported that pitting appeared on this type of stainless steel when the electrolyte temperature was about 40 °C.…”
Section: Literature Surveymentioning
confidence: 94%
“…Lu et al [ 39 ] also performed the synthesis on stainless steel type 904L. Several different voltages were used.…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…Among these films, highly porous oxide films formed on stainless steel is more promising candidate to act as nanoporous active materials, because they can provide high pseudo capacitance due to more reaction sites of large surface area nanostructured Fe2O3, and acceptable electrical conductivity of Fe3O4. However, the limited thickness of the anodic films on stainless steel substrates via galvanostatic anodization is generally restricting the mass of active materials [9][10][11][12][13]. Furthermore, the effects of film thickness on supercapacitance behavior of anodic oxide films have not been well studied because it is difficult for electrolyte ions to penetrate into thick nanoporous films.…”
Section: Introductionmentioning
confidence: 99%